Partition coefficient-Lewis basicity correlation in four dioxycyclobutenedion-bridged novel ball-type phthalocyanines - Yazici, Aysegul; Dalbul, Nida; Altindal, Ahmet; Salih, Bekir; Bekaroglu, Ozer (Elsevier Science Sa, 2016)
The novel ball-type bis-metallo [Zn(II), Co(II) and Cu(II)] phthalocyanines were synthesized from 4,4'(3,4-dioxocyclobut-l-ene-1,2-diyl)-bis(oxy)] diphthalonitrile, which can be obtained by the reaction of 4-nitrophthalonitrile with 3,4-dihydroxy-3cyclobuten-1,2-dione. The novel ball-type phthalocyanines with cyclobutene unit were characterized by elemental analysis, UV-vis, FT-IR, H-1 NMR, and MALDI-TOF mass spectroscopy. The response and recovery behaviours of the films to different analytes, which span a broad range of Lewis base, were investigated by utilizing an AT-cut quartz crystal resonator. Frequency changes during transient exposures to these vapours were rapid and reversible. The sensing behaviour of the films for a broad range of Lewis bases and the correlation between the partition coefficients and Lewis base enthalpies were investigated. Partition coefficients obtained from the linear response regimes of the calibration curves were in the 800-22,000 range. Results show that partition coefficients may be correlated exponentially with binding enthalpy. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Dioxycyclobutenedion bridged; Ball-type; Phthalocyanine; Partition coefficient; Lewis basicity; Gas sensing